2020
DOI: 10.1186/s40504-020-00102-6
|View full text |Cite
|
Sign up to set email alerts
|

How should researchers cope with the ethical demands of discovering research misconduct? Going beyond reporting and whistleblowing

Abstract: In this paper, I will argue that making it mandatory to report research misconduct is too demanding, as this kind of intervention can at times be self-destructive for the researcher reporting the misconduct. I will also argue that posing the question as a binary dilemma masks important ethical aspects of such situations. In situations that are too demanding for individual researchers to rectify through reporting, there can be other forms of social control available. I will argue that researchers should explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 40 publications
0
11
0
4
Order By: Relevance
“…More important than anything is for institutional leaders at all levels to "walk the talk": exert visible ethical leadership, lead by example and act according to the processes, policies and procedures they issue (Forsberg et al, 2018;LERU, 2020;Valkenburg et al, 2021;Vie, 2020;Winchester, 2018). Gopalakrishna, ter Riet and colleagues (2021) recently suggested that researchers often may subscribe to the norms of scientific integrity but nevertheless digress from those norms due to dissonance in their research environment.…”
Section: Walk the Talk!mentioning
confidence: 99%
See 4 more Smart Citations
“…More important than anything is for institutional leaders at all levels to "walk the talk": exert visible ethical leadership, lead by example and act according to the processes, policies and procedures they issue (Forsberg et al, 2018;LERU, 2020;Valkenburg et al, 2021;Vie, 2020;Winchester, 2018). Gopalakrishna, ter Riet and colleagues (2021) recently suggested that researchers often may subscribe to the norms of scientific integrity but nevertheless digress from those norms due to dissonance in their research environment.…”
Section: Walk the Talk!mentioning
confidence: 99%
“…However, a significant proportion of researchers does not know where or how to report instances of suspected misconduct (Moran et al, 2020). Less than half would feel comfortable doing so without fear of retaliation or personal impact (Moran et al, 2020) because they lack confidence in their institution's willingness or ability to investigate the case thoroughly and correctly, to take corrective action, or even to take the report seriously (Vie, 2020).…”
Section: Dealing With Integrity Breachesmentioning
confidence: 99%
See 3 more Smart Citations